Association of CRP and d-dimer with CT severity scoring in COVID-19 patients - Patel, Sunil Kumar; Adhikari, Shital; Gauli, Basanta; Bhattarai, Madhur Dev; Paudel, Bigyan; Adhikari, Deepak; Gurung, Sailesh; Wagley, Pratik; Puri, Niraj; Regmi, Bibek (Journal of Chitwan Medical College, 2021)
Background: Corona virus disease 2019 (COVID-19) has become a global public health issue with significant impacts upon the healthcare delivery systems. Previous studies have consistently found elevated levels of C-Reactive Protein and D-dimer with disease severity. In this study, we aimed to investigate the relationship between C-Reactive Protein, D-dimer level and Computed Tomography severity score in patients with SARS-COV-2 pneumonia. Methods: Our study included 76 patients with COVID-19, admitted in COVID Unit of Chitwan Medical College and Teaching Hospital from June 2020 to December 2020. We included COVID-19 cases confirmed by a RT-PCR test and those undergoing High resolution Computed Tomography of chest and having C-Reactive Protein and D-dimer levels done on admission. A semi-quantitative CT score was calculated based on the extent of lobar involvement (0:0%; 1, < 5%; 2:5–25%; 3:26–50%; 4:51–75%; 5, > 75%; range 0–5; global score 0–25. Results: Overall the median CTSS was 15. Mild, moderate and severe CT severity scoring was reported in 5.3%, 60.5% and 34.2% respectively and D-dimer progressively increased across the CTSS severity groups. The difference was significant for CRP, P = 0.007 but not for D-dimer, P = 0.42. Moreover, higher CTSS scores were significantly associated with higher ICU stay, lower recovery rate and higher O2 requirement at discharge. Conclusions: Radiological severity of COVID-19 pneumonia has significant association with elevated C-Reactive Protein level but not with D-dimer level and other routine laboratory parameters.